Postweaning growth of performance-tested buffaloes (Bubalus bubalis, Artiodactyla, Bovidae) reared under no-milking versus a dual-purpose system (2012)
ABSTRACT: the objective of this study was to compare growth traits in buffaloes reared in farms using a pre-weaning management system with no milking (NM), or a dual-purpose system (DP: meat and milk production). Methods: performance tests were conducted at the Experimental Station of the University of Antioquia, located in Barbosa (Antioquia, Colombia). Buffaloes were confined and fed with fresh Maralfalfa grass (Pennisetum sp.) ad libitum, plus two kilograms of mixed plus two 2 kilograms of concentrate supplement per day. Weight, ultrasound, and bovinometric measurements were taken every 14 d. Bovinometric measurements were chest girth (CG), height at withers (HW), and height at sacrum (HS). Ultrasound measurements were Longissimus muscle area (REA) and rump fat thickness (RFT). Traits were analyzed using a linear regression and second order polynomial model using unstructured variance-covariance matrices and accounting for relationships among animals. Results: all the traits in DP animals, as well as RFT, HW, and HS in NM animals fit well with a second-order regression mixed model. Weight, CG, and REA in NM animals fit well with a first-order regression mixed model. The rate of increase for HW and HS declined at the end of the test in NM animals, while weight, CG, RFT, and REA did not. The DP buffaloes displayed an accelerated rate of increase for all traits towards the end of the evaluation. The non-zero estimates of genetic variances for random regression effects suggests that these characteristics may be improved genetically in Colombia. Environmental and genetic differences among farms may have influenced the high variability among individuals for the intercept. Conclusions: the linear regression variances were small for all traits, suggesting that although selection of animals within these performance tests is possible, expected changes in the buffalo population will be small.